Los conceptos sensibilizadores y el nuevo movimiento metateórico - Abreu, Cláudio (El Colegio de México, 2020)
The notion of sensitizing concept is an important methatheorical tool to understand the development of sociological knowledge. However, it can contribute even more to metatheorical discussions. The thesis that motivates this study is that the conception of theory behind such discussions limits its potential. The aim of this article is to make explicit such limitation. The argumentative strategy is to present the advantages of a contemporaneous conception of theory. Once we expose the notion of sensitizing concept, we will discuss the phases of development of philosophy of science; two conceptions of scientific concepts; and the basic ideas of structuralist metatheory, of fundamental law of a theory and of testing of such laws. Then we carry out the analysis of the notion of sensitizing concept. The conclusion is that, using as a background structuralist metatheory, the notion of sensitizing concept is enhanced.